Mengenal Lembaga Pendidikan Dasar Kuttab Periode Klasik - Musfa Rahmani; Siti Fatimah; Noviana Berampu; Fathma Kurniati Lubis (Yayasan Rahmat Islamiyah, 2020)
This article discusses the Kuttab as the Institute of Islamic Education in the classical period, from the time of the Prophet to the city of Baghdad destroyed by Hulago Khan (650 AD-1250 AD). This research method uses library research methods by studying various reference sources to obtain complete and reliable data. The results of this study state that Kuttab is the first basic educational institution in the Islamic world. The Kuttab place of education began in the homes of a teacher, then moved to the mosque yard and built a separate building. The subject matter at Kuttab was originally a lesson in reading and writing using Arabic which means good, then coupled with lessons in reading and memorizing the Koran and understanding the principles of teaching Islam.Keywords: Kuttab, Institution, Classical Period.